Is Exercise Adherence Associated with Clinical Outcomes in Patients with Advanced Heart Failure? - Evangelista, Lorraine S. (2010)
BACKGROUND: There is limited research to support the effect of exercise adherence on clinical outcomes in patients with heart failure (HF). This secondary analysis was conducted on the intervention arm of an exercise training study in patients with HF to assess whether adherence and the dose of treatment exposure were associated with clinical outcomes, functional performance (maximum oxygen consumption [VO(2)], anaerobic threshold, and workload), and quality of life (QOL). METHODS: Seventy-one patients (average age, 54.0 ± 12.5 years; male, 66%; Caucasian, 66%; married, 61%; New York Heart Association class II III, 97.2%; and average ejection fraction, 26.4% ± 6.5%) were included in the current study. Patients with an increase ≥ 18% in the amount of exercise from baseline to 6 months, as measured by pedometers, were categorized as adherers (n = 38); patients who had no change or an increase in the amount of exercise of < 18% were categorized as nonadherers (n = 33). RESULTS: The 2 groups were significantly different in the composite endpoint of all-cause hospitalization, emergency room admissions, and death/urgent transplantation (hazard ratio, 0.31; confidence interval, 0.159–0.635; P < 0.001). Adherers had greater improvements in functional performance and QOL compared with nonadherers (P < 0.001). CONCLUSION: These findings suggest that among patients with advanced HF, adherence to exercise is associated with more favorable clinical outcomes. There is also a positive dose-response relationship between the amount of exercise performed and improvement in functional performance and QOL.